Synergistic strengthening mechanism of Portland cement paste reinforced by a triple hybrid of graphene oxide, functionalized carbon nanotube, and nano-silica. (17th October 2022) - Kim, Gyeongryul; Suh, Hyeongwon; Cho, Seongmin; Im, Sumin; Nezhad, Erfan Zal; Seok, Seungwook; Choi, Changsik; Bae, Sungchul
Highlights: Triple hybrid of GO, f-CNT, and NS as a cement composite reinforcement was studied. Amount of GO was selected as a variable in the triple hybrid. Optimal ratio of GO for the triple hybrid was found to be 0.04 wt% (of cement) Dispersion of the triple hybrid depends on the bonds between the nanomaterials. Hydration and mechanical properties of cement composites are affected by dispersion of the triple hybrid. Abstract: This study investigates the synergistic strengthening mechanism of graphene oxide (GO), functionalized carbon nanotubes (f-CNT), and nano-silica (NS) triple hybrid-reinforced Portland cement composite. GO was selected as the variable owing to the synergistic effect of GO with both f-CNTs and NS upon dispersion by forming bonds with both nanomaterials. At a low GO dosage (∼0.03 wt% of cement), the bond between GO and NS deteriorated the dispersion in Ca 2+ -rich solution due to the overly attached NS on the GO surface. The highest GO fraction (0.05 wt%) also led to poor dispersion as the excess GO was agglomerated by Ca 2+ ions. However, an optimal amount of GO (0.04 wt%) significantly improved the dispersion quality. The enhanced dispersion of the triple hybrid positively influenced the hydration degree and mechanical performance of the cement paste (133 % and 156 % for compressive and tensile splitting strength compared to OPC) and the pozzolanic reactivity of NS.